1996
DOI: 10.1111/j.1600-0714.1996.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 27 in adult human third molar dental pulp

Abstract: This study is the first to define the expression of hsp 27 in the pulp of the adult human third molar. Using a monoclonal antibody against human hsp 27, immunoreactivity was demonstrated in the odontoblasts, odontoblast processes, pulp fibroblasts, and smooth muscle and endothelial cells of vessel walls. Nerves were negative. Pulp fibroblasts were characterized by cytoplasmic staining and variable nuclear staining. Odontoblasts also displayed consistent cytoplasmic staining and variable nuclear staining. Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, in our search for literatures, no study has been conducted so far examining the expression of HSPs during cytotoxic changes in pulp cells. Sens et al [15] reported the expression of HSP in odontoblasts, odontoblast's processes (dentinal fibers), dental pulp fibroblasts, endothelial cells, and vascular smooth muscle cells in human 3rd molars. Further, Tate et al [16] and Suzuki et al [17] verified the expression of HSP in dental pulp cells after experimental cavity preparation by laser ablation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our search for literatures, no study has been conducted so far examining the expression of HSPs during cytotoxic changes in pulp cells. Sens et al [15] reported the expression of HSP in odontoblasts, odontoblast's processes (dentinal fibers), dental pulp fibroblasts, endothelial cells, and vascular smooth muscle cells in human 3rd molars. Further, Tate et al [16] and Suzuki et al [17] verified the expression of HSP in dental pulp cells after experimental cavity preparation by laser ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent incisors grow continuously throughout life, so the difference in tooth type may account for the discrepancy in the immunoreactions. Sens et al (1996) demonstrated the presence of HSP 25 in odontoblasts in the human third molar, and proposed that HSP 25 has a role in the protection and recovery of odontoblasts from daily environmental extremes experienced in the oral cavity. The constant and intense expression of HSP 25 in odontoblasts at the crown portion of the rat molar is similar to that in the rat incisor (Ohshima et al, 2000, 2001), which is consistent with Sens et al's (1996) hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sens et al (1996) demonstrated the presence of HSP 25 in odontoblasts in the human third molar, and proposed that HSP 25 has a role in the protection and recovery of odontoblasts from daily environmental extremes experienced in the oral cavity. The constant and intense expression of HSP 25 in odontoblasts at the crown portion of the rat molar is similar to that in the rat incisor (Ohshima et al, 2000, 2001), which is consistent with Sens et al's (1996) hypothesis. Thus, HSP 25 has appreciable roles in both the morphological changes of young odontoblasts during odontogenesis, and in the protection and recovery of mature odontoblasts at the crown portion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat shock proteins represent a family of constitutive and inducible proteins, the expression of which may enhance the ability of cells to withstand stress or which may signal up-regulation of reparative responses during cellular injury [Ang et al, 1991]. The expression of heat shock proteins in odontoblasts and various cells of the pulp [Sens et al, 1996[Sens et al, , 1997 indicates that they are possibly involved in resisting injury during cellular stress. It will be interesting to examine heat shock protein expression during caries beneath lesions of varying activity.…”
Section: Injury Responses In the Dentine-pulp Complexmentioning
confidence: 99%